Development of bioreactors for enrichment of chemolithotrophic methanogen and methane production - Na, B.K.; Tae, S.H.; Sung, H.L.; Ju, Donghun; Sang, Byung In; Doo, H.P. (2007)
A gas-circulating bioreactor was used for enrichment of autotrophic methanogens. Mixture of hydrogen and carbon dioxide (5:1) was used as a sole energy and carbon source. Anaerobic digestive sludge isolated from wastewater treatment system was inoculated into the gas-circulating bioreactor. The enrichment of two chemolithotrophic methanogens, Methanobacterium curvum and Methanobacterium oryzae was accomplished in the gas-circulating bioreactor. The enriched bacteria were cultivated in a bioreactor equipped with hollow-fiber hydrogen-supplying system (hollow-fiber bioreactor), and a hybrid-type bioreactor equipped with hollow-fiber hydrogen-supplying system and electrochemical redox control system. The methane productivity was maximally 30% (V/V) in the hollow-fiber bioreactors and 50% (V/V) in the hybrid-type bioreactor.
Keywords: carbon dioxide; hydrogen; methane; article; autotrophy; bioreactor; chemolithotroph; electrochemistry; energy resource; hollow fiber; inoculation; Methanobacterium; methanogen; nonhuman; oxidation reduction reaction; sludge digestion; waste water management; Methanobacterium curvum; Methanobacterium oryzae